Distribution patterns, richness, endemism and conservation of Phyllanthaceae in the Atlantic Forest of Northeastern Brazil - Lima, Vitória Raquel S.; Maciel, Jefferson R.; Torres, Alícia M. [UNESP]; Athiê-souza, Sarah M. (Academia Brasileira de Ciências, 2025)
Brazil’s Atlantic Forest is one of the most important biodiversity hotspots on the planet, home to several rare and endemic species. The Phyllanthaceae family harbors great richness of endemic species in this area, including some recently described in the Northeastern Atlantic Forest. However, this biome faces serious threats due to human activity, habitat loss and species extinction. This study analyzed the distribution, richness and endemism of Phyllanthaceae species in the Northeastern Atlantic Forest, investigated the relationship between species richness and climatic characteristics, and delimited the centers of endemism and the main threats and pressures. Data from Reflora, Specieslink, herbaria from the Brazilian Northeast and specialized literature were used. Generalized linear models analyzed the relationship between species richness and climate variables. Forty-two species were identified in the study area, 13 of which are endemic. The south of Bahia state stood out for its greater species richness, with 23 species described, including 11 endemic ones. Three centers of endemism were identified: two in southern Bahia and one in Pernambuco state. Most endemic species face threats, with few protected areas. Deforestation, agriculture and urban expansion represent the main pressures on these species in the region.
Keywords: biogeography; climate change; Malpighiales; Phyllanthoideae